(untitled) (Research, Society and Development, 2020)
In obtaining smaller plants the use of plant regulators such as paclobutrazol (PBZ) are used, however, there are currently no reports on the development of ornamental pineapple produced by plants treated with PBZ, whereby the objective of this work was to evaluate the influence of PBZ on plant development to obtain smaller ornamental pineapple plants. In this sense, an experiment was carried out with a randomized block design, in a factorial arrangement of 3x4 subdivided plots, with three types of plants (arial sucker and plant sucker treated with PBZ and arial sucker of plants not treated with PBZ), with four seasons, eight replicates and four plants per plot. In each season, the number of leaves, width and length of leaf D, height and diameter of the plant base were evaluated. The sucker-type plants treated with PBZ showed the highest growth rate and the greatest influence of the PBZ hormone. Since the hormone has a residual effect that can be transmitted to organs of sexual reproduction according to its ubiquation in the matrix plant, affecting its initial development.